Análise in vivo da osteocondutividade de biomateriais a base de colágeno, hidroxiapatita e queratina derivados de subprodutos da indústria avícola - Guerrero, Jesús Alberto Pérez (2019)
The Brazilian poultry industry generates abundant byproducts of low economic value that have the potential to be transformed into osteoconductive biomaterials for the clinical treatment of extensive bone defects that still remains a public health problem and challenges the biotechnology industry in the development of new biomaterials. The objective of this work was to evaluate in vivo biologically the osteoconductivity of biomaterials, produced from poultry industry waste for bone repair. Four UV / riboflavin crosslinked collagen based hydrogels (Col) and varying concentrations of hydroxyapatite (HA) and keratin (Q) were tested. Male Wistar rats (n = 60) were randomly divided into 6 groups and evaluated at 1 and 3 month experimental times (5 rats / treatment). For each animal a critical size defect of 8 mm diameter was created in the skull, filled with one of the following experimental conditions: 100% Col (G1), 90% Col + 10% HA (G2), 90% Col + 10% Q (G3), 90% Col + 5% HA + 5% Q (G4), autogenous bone (C +) and blood clot (C-). After excisional necropsies and histological processing, the obtained slides were analyzed by histomorphometry using the Image J. program. For the parameters neoformed bone, connective tissue, biomaterial, old bone or other structures, the percentage density was tabulated and expressed as mean (± standard deviation ) and analyzed statistically using the parametric ANOVA test and Dunnet's post-test considering significant differences if P <0.05. Bone neoformation at 1 month was lower for all test materials and C- for C +, 19.3% (± 1.6), as well as at 3 months for G1, G3, G4 and C- in relation to C + , 21.8% (± 4.6). The presence of connective tissue was higher for all test materials compared to C + in 1 and 3 months, respectively 30.8% (± 11.5) and 32.1% (± 9.1). The presence of the biomaterial at 1 month was lower for G1, G2 and G3, almost absent for G4 and absent for C-, in relation to C + [19.9% ​​(± 8.2)], at 3 months for G2 it was lower and absent for G1, G3, G4 and C- in relation to C + [17.5% (± 5.2)]. For old bone and other structures there were no differences between the test materials in relation to C + and C-. The biomaterials tested showed low osteoconductivity and high biodegradability, with G2 having the highest potential of biotechnological development as a membrane of guided bone regeneration.